Szkolne nauczanie religii rzymskokatolickiej jako miejsce motywowania młodzieży do chrześcijańskiego działania - Zellma, Anna (Poznańskie Studia Teologiczne, 2013)
The teaching of the Roman Catholic religion at school involves a variety of didactic, educational and evangelizing measures. Among them special care is taken to support students in developing motivation for Christian action. The scope of this catechetical activity has been clearly defined in curriculum documents for religious education, referred to in the core curriculum of catechesis and the religious education syllabus. The paper analyzes the teaching of the Roman Catholic religion at school as a means conducive to motivating young people to Christian action. First, the nature of the teaching of the Roman Catholic religion in middle school and high schools is indicated. In this context, attention is drawn to the core curriculum in the aspect of motivating young people to Christian action. The following factors are presented in a sequence: goals, objectives and content of religious education as well as guidance how to achieve the objectives of the curriculum related to the above-mentioned are of work of the religion teacher. A brief concluding section includes, besides a synthesis of the discussed points, indications concerning empirical research.